Adoption and acceptance of harvesting technology for smallholder in Felda Tun Ghaffar, Jasin, Melaka / Muhammad Airil Haimi Azahar - Azahar, Muhammad Airil Haimi (Faculty of Plantation and Agrotechnology, 2017)
Plantation sector in Malaysia especially the oil palm plantation has used technology for various purposes. Two main reasons for the smallholder to use the technology is for enhance their production of fresh fruit bunches (FFB) and efficiency in their work. A study was conducted to investigate the current acceptance and adoption of the harvesting technology among the dependent smallholder by using survey and questionnaire method. The objectives of this study are to investigate the most influential factors that affecting the acceptance and adoption of technology and the impact of harvesting technology on smallholder’s performance. 87 smallholders based on Krejcie and Morgan sampling table is used as the population there are only 108 smallholders. There were four independent variables to study the acceptance and adoption of the harvesting technology which were cost of technology, job relevance, satisfaction and information from surrounding. All of the independent variables significantly correlated with the smallholder’s acceptance and adoption except for the factor of cost of technology. These variables indicate only influence 17.1% from the objectives by using regression analysis. Using technologies to improve lifestyle is a must and to increase efficiency and productivity, harvesting technology surely can help the smallholder to gain their goals. Smallholder must value the technology and alert with the current situations as the technology nowadays is so beneficial to the sector that contain high workload.